2020
DOI: 10.1037/edu0000454
|View full text |Cite
|
Sign up to set email alerts
|

The individual stem student in context: Idiographic methods for understanding self-knowledge and intraindividual patterns of self-efficacy appraisal.

Abstract: This study aimed to identify elements of personal knowledge that were hypothesized to underlie within-person, across-context variations in students' appraisals of self-efficacy for coping with challenges encountered in Science, Technology, Engineering, and Mathematics (STEM) education. Freshman in a college of engineering completed assessments of (a) 4 elements of personal knowledge regarding themselves and their educational resources; (b) their subjective beliefs about links between these 4 personal and socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 90 publications
(136 reference statements)
1
15
0
5
Order By: Relevance
“…It is also possible that some common traits emerge or are applicable for all persons, and some additional traits that are unique for only one individual. This possibility would resemble what was found in the course of the development of the Chinese Personality Assessment Inventory (Cheung et al, 1996). Using the lexical approach, traits unique to the Chinese culture like Harmony, Ren Qin (Relationship) Orientation, Face and Thrift Extravagance emerged in addition to common traits like Emotionality and Introversion–Extraversion.…”
Section: How Can Big Data Fuel An Idiographic Personality Science?supporting
confidence: 63%
See 1 more Smart Citation
“…It is also possible that some common traits emerge or are applicable for all persons, and some additional traits that are unique for only one individual. This possibility would resemble what was found in the course of the development of the Chinese Personality Assessment Inventory (Cheung et al, 1996). Using the lexical approach, traits unique to the Chinese culture like Harmony, Ren Qin (Relationship) Orientation, Face and Thrift Extravagance emerged in addition to common traits like Emotionality and Introversion–Extraversion.…”
Section: How Can Big Data Fuel An Idiographic Personality Science?supporting
confidence: 63%
“…Although Windelband (1904) did not restrict the idiographic approach to the study of individual persons, the call for a careful analysis of the individual person as an alternative to the analysis of aggregates was echoed throughout the history of personality psychology (Allport, 1937; Beck, 1953; Beck & Jackson, 2020a; Carlson, 1971; Lamiell, 1981; Magnusson, 2001; Shoda, Mischel, & Wright, 1994; Stern, 1911), and there are indeed idiographic studies in personality science that are but low in number compared with the vast amount of nomothetic research (e.g. Allport, 1965; Beck & Jackson, 2020a; Cervone, Mercurio, & Lilley, 2020; Grice, 2004; Hermans, 1988; Karch, Sander, von Oertzen, Brandmaier, & Werkle‐Bergner, 2015; Nasby & Read, 1997; Pelham, 1993; Schmitz & Skinner, 1993; Shoda et al, 1994; Simonton, 1998).…”
mentioning
confidence: 99%
“…We focus on research and practice in clinical psychology/psychotherapy and work/organizational psychology as major applied disciplines in psychological science. Studies on dynamic personality phenomena in educational settings also exist (e.g., Cervone, Mercurio, & Lilley, 2020; Zhang, Beckmann, & Beckmann, 2019) but remain sparse.…”
Section: Personality Dynamics In Applied Settingsmentioning
confidence: 99%
“…Undergraduate students studying music volunteered to take part in the research. Of the 84 students, 68 identified as completely female on the 11-point gender scale (Cervone et al, 2020;Haupert, 2019), and 13 identified as completely male, two identified in the middle of the gender scale (choosing 5) and one person reported not identifying on the scale. Students represented a range of year groups, with 48 (57.1%) first year, 25 (29.8%) second year, 8 (9.5%) third year, and 3 (3.6%) fourth year students.…”
Section: Participantsmentioning
confidence: 99%